Nilai Ekonomi dan Produktivitas Alat Tangkap Perikanan - Adhawati, Sri Suro; Cangara, Arie Syahruni; Fakhriyyah, Sitti; Kamaruddin, Kamaruddin; Aswin (Jurnal Samudra Ekonomi dan Bisnis, 2023)
The income of coastal communities as fishermen is relatively low because the economic activity of the fishing gear used is not yet optimal. This study aims to analyze the economic value and productivity of fishing gear that provides optimal income. The research was conducted in two coastal districts of Bone Bay, namely Tellu Siattinge and Kajuara. The location was determined purposively with the consideration that the Tellu Siattinge area is in the north while the Kajuara area is in the south. This type of survey research uses qualitative and quantitative analysis methods. The research results stated the fishing gear with the highest economic value was the purse seine type in the Kajuara District and the bagan cungkil type in the Tellu Siattinge District. The second result identified that the fishing gear that had the highest productivity was the bagan tancap type in Kajuara and the bagan cungkil type in Tellu Siattinge waters.